2011
DOI: 10.1007/s00167-011-1525-x
|View full text |Cite
|
Sign up to set email alerts
|

Previous fracture surgery is a major risk factor of infection after total knee arthroplasty

Abstract: This study identified previous history of fracture and remnants of internal fixation as major risk factors of infection after TKA. For clinical relevance, surgeons should be aware of potential infection when performing TKA in patients with these risk factors and patients should be informed of the potential risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 19 publications
(54 reference statements)
4
44
0
3
Order By: Relevance
“…Suarez et al and Hossain et al both found that infection led to a majority of revision failures (46% and 31%, respectively), especially those failures that occurred earlier after surgery 31,32 . This likely affirms many surgeons' qualms about performing multiple surgical procedures on the same joint, as the risk of infection is greater with each subsequent procedure 34,35 . Overall, our study showed a relatively poor six-year cumulative survivorship of revision total knee arthroplasties in the younger (71%) and older (66%) groups.…”
Section: Revision Total Knee Arthroplasty I N T H E Young Pat I E N Tmentioning
confidence: 61%
“…Suarez et al and Hossain et al both found that infection led to a majority of revision failures (46% and 31%, respectively), especially those failures that occurred earlier after surgery 31,32 . This likely affirms many surgeons' qualms about performing multiple surgical procedures on the same joint, as the risk of infection is greater with each subsequent procedure 34,35 . Overall, our study showed a relatively poor six-year cumulative survivorship of revision total knee arthroplasties in the younger (71%) and older (66%) groups.…”
Section: Revision Total Knee Arthroplasty I N T H E Young Pat I E N Tmentioning
confidence: 61%
“…They observed significantly more frequent infections with open reduction and internal fixation after trauma to the knee joint and when osteosynthesis material remained in situ [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito que la cirugía de fracturas previa es un factor que incrementa el riesgo de infección en artroplastias de rodilla 9 . Este hecho iría a favor de la intervención de las 2 enfermedades a la vez, disminuyendo así el alto riesgo de infección que ya presentaba la paciente.…”
Section: Discussionunclassified